Music collecting behavior and experience in the streaming era in Brasil - Prado Filho, José Roberto (2018)
This study examines music collecting behavior and experience in the streaming era. Twelve in-depth, qualitative interviews were carried out to explore the nature of analog music collecting in Brazil and to understand the relationship between the physical objects and the collectors. The evidence suggests that music collectors do identify with the term collector and their sense of Self is derived from it. The way music is consumed will vary depending on the occasion, with streaming being used on the go and vinyls and cds as a ritual to be performed at home, as collectors have a need to touch the objects and enjoy the music as a whole experience. There is a prevalence of masculine behavior in collecting. The collecting behavior can be seen by some as addictive and collectors will show signs of addiction often times. Buyers will show conflicting patterns, varying from rational to emotional purchasing behaviors. As collectors started to acquire their objects in early teenage years, their music taste today is the same genre as that time of their lives. There is an element of nostalgia in their current music consumption, often times to fulfill a wish that could not be satisfied at the time for lack money or lack of access. The topic is relevant for any music businesses, analog or digital, such as record label, music and memorabilia e-commerce, streaming services, collector groups and auction platforms, considering music consumption is broad and can be economically explored in many different ways.